Aggressive Treatment of Vitamin D Deficiency in Hispanic and African American Critically Injured Trauma Patients Reduces Health Care Disparities (Length of stay, Costs, and Mortality) in a Level I Trauma Center Surgical Intensive Care Unit - L Ray Matthews; Yusuf Ahmed; Omar Danner; Michael Williams; Carl Lokko; Jonathan Nguyen; Keren Bashan-Gilzenrat; Diane Dennis-Griggs; Nekelisha Prayor; Peter Rhee; Ed W Childs; Kenneth Wilson; et al. (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2017)
Background: Socioeconomics only account for 18% of all healthcare disparities. Healthcare disparities in the intensive care unit (ICU) have been well documented and persist in spite of previous government and medical interventions. Vitamin D deficiency is the most common nutritional deficiency in the United States and the world. This deficiency has been largely overlooked in the debate on healthcare disparities. Hypothesis: We hypothesize that low vitamin D levels (a steroid hormone that activates CD4, a T-cell for immune response) and a low CD4 cell count (a T-cell and a marker of a weak immune system) account for most of these healthcare disparities seen in Hispanic and African American patients. We further hypothesize that aggressive treatment of vitamin D deficiency decreases intensive care unit (ICU) length of stay (LOS), ICU cost, and mortality rate in this patient population. Methods: We performed a prospective study of the vitamin D status on 316 Hispanic and African American patients admitted to Grady Hospital SICU from August 2009 to September 2011. The patients were divided into 3 groups: Group 1 was treated with vitamin D 50,000 international units (IU) weekly, orally or nasogastric tube (50,000-400,000 IU) for up to 8 weeks; Group 2 was treated with vitamin D 50,000 IU daily for 5 days (250,000 IU of vitamin D); and Group 3 patients (aggressive treatment) received vitamin D 50,000 IU daily down the nasogastric tube for 7 consecutive days. The injury severity score (ISS) was a mean of approximately 15 in all three groups. There wasn't ant statistical difference between the three groups in terms of injury severity. A CD4 cell count was measured in a subset of 180 patients to evaluate as a marker for potential immune system compromise or weak immune system. In our surgical intensive care unit, Hispanic and African American patients had lower vitamin D levels and CD4 counts up to 40% lower than Caucasian Americans. Results: The mean vitamin D levels for the three groups were as follows: Group 1, 10.22±0.60 ng/ml; Group 2, 13.78±0.72 ng/ml; and Group 3, 15.89±0.87 ng/ml (normal≥ 40 ng/ml). Mean ICU LOS decreased with aggressive treatment of vitamin D deficiency from 13.21±2.04 days in Group 1 to 11.53±2.45 days in Group 2 to 6.3 ±0.79 days in Group 3 (p-value, 0.021). Mean ICU cost also decreased with aggressive treatment of vitamin D deficiency by the following: Group 1, $50,934.25±7, 8776; Group 2, $44,464.50±9,458.50; and Group 3, $24,433.02±2,887.75 (p-value, 0.021). Mortality rate decreased from 11.0% in Group 1 to 9.4% in Group 2 to 6.4% in Group 3 (p-value, 0.486). This trend shows a clinically significant 42% reduction in mortality rate which is clinically significant even though it is not statistically significant.  Conclusion: We conclude that a compromised immune state due to low vitamin D status and low CD4 cell count may explain a large percentage of healthcare disparities. Aggressively optimizing serum vitamin D status to ≥ 40 ng/ml may be the one of the most important steps in solving healthcare disparities in the United States. Further studies on low vitamin D levels/low CD4 counts are needed to fully address healthcare disparities.